Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Speciation with gene flow in a narrow endemic West Virginia cave salamander (Gyrinophilus subterraneus) - Evan H. Campbell Grant; Kevin P. Mulder; Adrianne B. Brand; Douglas B. Chambers; Addison H. Wynn; Grace Capshaw; Matthew L. Niemiller; John G. Phillips; Jeremy F. Jacobs; Shawn R. Kuchta; Rayna C. Bell (Conservation Genetics, 2022)

Temporal Trends in Polybrominated Diphenylethers (PBDEs) in Blubber of Ringed Seals (Pusa hispida) from Ulukhaktok, NT, Canada Between 1981 and 2015 - R. F. Addison; D. C. G. Muir; M. G. Ikonomou; C. Dubetz; T. G. Smith; J. Alikamik (Archives of Environmental Contamination and Toxicology, 2020)

Boundary spanning at the science–policy interface: the practitioners’ perspectives - A. T. Bednarek; C. Wyborn; C. Cvitanovic; R. Meyer; R. M. Colvin; P. F. E. Addison; S. L. Close; K. Curran; M. Farooque; E. Goldman; D. Hart; H. Mannix; et al. (Sustainability Science, 2018)

Association mapping reveals loci associated with multiple traits that affect grain yield and adaptation in soft winter wheat - Dennis N. Lozada; R. Esten Mason; Md Ali Babar; Brett F. Carver; Gina-Brown Guedira; Keith Merrill; Maria Nelly Arguello; Andrea Acuna; Lucas Vieira; Amanda Holder; Christopher Addison; David E. Moon; et al. (Euphytica, 2017)

Ancient river systems and phylogeographical structure in the spring salamander, Gyrinophilus porphyriticus - Shawn R. Kuchta; Michael Haughey; Addison H. Wynn; Jeremy F. Jacobs; Richard Highton (Journal of Biogeography, 2016)
Aim The river drainages of the Appalachian Mountains have experienced a dynamic history as glacial cycles, stream capture and other geological processes have led to the fragmentation and fusion of formerly isolated palaeodrainages. Some ancient rivers have gone extinct, including portions of the great Teays River. Here we investigate the contribution of contemporary and historical drainages to patterns of phylogeographical structure in the spring salamander complex, Gyrinophilus porphyriticus . Location Eastern North America, USA . Methods Sampling spanned the range of the G. porphyriticus complex, and included representative samples of the cave species of Gyrinophilus as well. Molecular sequence data included the mitochondrial DNA locus cytochrome b and the nuclear locus recombination‐activating gene 1 ( RAG ‐1). Time‐calibrated phylogenies were inferred, and Bayes‐ LAGRANGE was used to reconstruct ancestral distributions. Contemporary and historical river influences on patterns of genetic diversity were tested using distance‐based redundancy analysis (db‐ RDA ). Results The G. porphyriticus complex originated prior to the Pleistocene glacial cycles, and historical river systems explained more genetic variation than did contemporary drainages or geographical distance. Patterns of genetic variation suggest that extinct or remodelled palaeodrainages, including the Teays River, played an important role in structuring contemporary patterns of genetic variation. Main conclusions The hydrogeological history of eastern North American drainage basins has been instrumental in structuring patterns of regional biodiversity in freshwater species. Here we show that hydrological remodelling has also left its genetic signature in the semi‐aquatic spring salamander complex, G. porphyriticus . Historical drainages accounted for the largest fraction of phylogeographical structure, more so than did contemporary drainages or geographical distance, with spatial and temporal patterns of variation associated with the extinct Teays River.

Carry-over effects and foraging ground dynamics of a major loggerhead breeding aggregation - Simona A. Ceriani; James D. Roth; Anton D. Tucker; Daniel R. Evans; David S. Addison; Christopher R. Sasso; Llewellyn M. Ehrhart; John F. Weishampel (Marine Biology, 2015)

The fate of 2-, 3-, and 4-chlorobiphenyl following intravenous administration to the Thorny Skate (Raja radiata) and the Winter Skate (Raja ocellata) - M. E. Zinck; R. F. Addison (Archives of Environmental Contamination and Toxicology, 1974)